Réduire La Peur Et Motiver Les élèves En Enseignant Le Français Autrement - Ameur, Azzeddine (El Omda in Linguistics and Discourse Analysis, 2025)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a1ca0f09-cbfb-4a3f-b24c-0720d88bbc5e-0" data-turn-id-container="request-WEB:a1ca0f09-cbfb-4a3f-b24c-0720d88bbc5e-0" data-testid="conversation-turn-2" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="297aa244-ff0c-4bf4-b770-9929b872f7c2" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> In this article, we review the various characteristics and outcomes of an experiment conducted by a team of teachers in several schools in the wilaya of M’sila. This study aims to improve students’ perception of this language and enhance their profiles. The results were entirely satisfactory, given the conditions and resources provided.